CLASSDOJO AS A TOOL FOR PROGRESSIVE ISLAMIC DA'WAH: AN ANALYSIS OF ELEMENTARY SCHOOL TEACHERS' COMPETENCIES AND CHALLENGES - Choirun Nisa; Najwa Ulfa Rafiah; Hanif Ar- Rif’an (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to analyze the competencies of Muhammadiyah elementary school teachers in integrating progressive Islamic da’wah through the use of ClassDojo and to identify various challenges in its implementation. The study employed a descriptive qualitative approach with a case study design in Pacitan Regency. Data were collected through in-depth interviews, observations, focus group discussions, and document analysis involving 20 teachers, school principals or coordinators, and parents. The results show that most teachers view the reinforcement of spiritual values and character as an important part of learning and see ClassDojo as a potential tool to support the cultivation of positive behaviors, communication between the school and parents, and the reinforcement of Islamic values such as discipline, responsibility, empathy, and good manners. In terms of competencies, teachers demonstrated fairly strong proficiency in pedagogical, professional, and social aspects; however, strengthening spiritual competencies and digital literacy still requires further attention. This study also identified several implementation challenges, including limited access to the internet and devices, varying levels of teachers’ proficiency in operating the app, suboptimal support from school policies, as well as potential issues regarding ethics, privacy, and the dilution of the educational value of guidance when children’s behavior becomes overly focused on the point system. Thus, the use of ClassDojo within the framework of progressive Islamic da’wah holds great potential for strengthening character education in Muhammadiyah elementary schools, but it requires support in the form of teacher training, reflective pedagogical design, and ethical and context-appropriate governance of the digital platform’s use.